-6x+7(3x-6)=177

Simple and best practice solution for -6x+7(3x-6)=177 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6x+7(3x-6)=177 equation:



-6x+7(3x-6)=177
We move all terms to the left:
-6x+7(3x-6)-(177)=0
We multiply parentheses
-6x+21x-42-177=0
We add all the numbers together, and all the variables
15x-219=0
We move all terms containing x to the left, all other terms to the right
15x=219
x=219/15
x=14+3/5

See similar equations:

| 4x+44=11 | | 8y–3=69 | | 2+14x=20x+1.5 | | 2/3h=-16 | | 40=5(z-3) | | 3/2w-5/3=-3/2 | | 7m-11=4+2m | | x+67=92 | | 6x-5(6x+39)=153 | | 7(x)=x+6 | | 8x+8x=-1 | | (3x2-5x+1)=(x2+4x+2) | | 25c2-12=1 | | 24-5-10a=-3(4-7a | | 9y–5=22 | | 8x+8x1=-1 | | x-(52-x)=20 | | 15c=90;c=6 | | -1(-2x+1)=9-14x | | 6x-65=3x+13 | | 3(4n+2)=-2(4n+6) | | -9x+30=-5(x+2) | | (8x+9)=(11x+12) | | 2(6x-3)=7(7x-1.2) | | 115+(x+27)=180 | | (4v-3)(v-5=) | | –8s+7=–7s | | 26=6k | | 7(x+5)=24 | | |5m+9|=-31 | | -4r+8+5=-15-3r | | 5w+8.6=-3.4 |

Equations solver categories